Correlation Between Learning Styles And Academic Achievement - Nurul Hidayah; Rofiqoh Rofiqoh; Anjar Kusuma Dewi; Aminah Suriaman (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
This study aims to find a correlation between students’ learning styles and academic achievement. The research subjects were students in class E of batch 2018, the academic year 2021–2022, in English Education Study Program, Tadulako University. The instruments used to collect the data were a questionnaire and students' transcripts. SPSS 20th version was used to analyze the data. The data analysis results indicate a moderate positive correlation between students' learning styles and academic achievement. It implies that learning style is not the main factor contributing to the student's academic achievement. The result of the student's learning styles also shows that, of all the types of learning styles, the visual learning style is found as the dominant learning style for the student's academic achievement.